2022
DOI: 10.3390/jcm11051401
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Management of Headache Disorders in US Emergency Departments: Analysis of 2007–2018 National Hospital Ambulatory Medical Care Survey Data

Abstract: We examined trends in management of headache disorders in United States (US) emergency department (ED) visits. We conducted a cross-sectional study using 2007–2018 National Hospital Ambulatory Medical Care Survey data. We included adult patient visits (≥18 years) with a primary ED discharge diagnosis of headache. We classified headache medications by pharmacological group: opioids, butalbital, ergot alkaloids/triptans, acetaminophen/nonsteroidal anti-inflammatory drugs (NSAIDs), antiemetics, diphenhydramine, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 73 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Moreover, managing socioeconomic and family-related stressors plays a crucial role in managing the effects of persistent PCS [ 49 , 59 ]. Furthermore, pharmacological treatment [ 60 ], such as acute or preventive medications for primary headache disorders, is useful [ 19 , 25 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, managing socioeconomic and family-related stressors plays a crucial role in managing the effects of persistent PCS [ 49 , 59 ]. Furthermore, pharmacological treatment [ 60 ], such as acute or preventive medications for primary headache disorders, is useful [ 19 , 25 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this, some of the most severe TBI patients can survive with impaired neurological function [ 23 ]. Moreover, because of the long-term effects of TBI, early follow-up and further rehabilitation are essential to facilitate recovery [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our study shows that opioids are prescribed mostly as treatment for acute migraine attacks, by a variety of physicians and also in an emergency setting where migraine subjects seek acute help for their headaches. Previous studies have concluded that prescribing opioids for migraine attacks in an emergency setting in the United States is common (25). While a cross-sectional study in the US showed that opioid use decreased from 2007 to 2018 among headache-related ER visits, it is still high (up to 28%) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we gradually increase the number of hospitals by keeping the number of records constant, based on 4,000. 36 All the simulations have been done on the MATLAB simulator.…”
Section: Algorithm For Encryption/descriptionmentioning
confidence: 99%